2020
DOI: 10.1007/s11701-020-01115-1
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the need for overnight admission after robotic-assisted laparoscopic prostatectomy

Abstract: Robotic-assisted laparoscopic prostatectomy (RALP) is the gold standard for the surgical management of localized prostate cancer (PCa). Multi-institutional series have demonstrated complications and readmissions in less than 5% of patients and most are now discharged within 24 h of surgery. Recently, several high-volume surgeons demonstrated the safety of sameday discharge (SDD) after RALP. The main benefits include lower costs and reduced exposure to nosocomial infections and hospital errors. The leading argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Recent research in the field suggests that a single night's stay or same-day discharge might be possible for selected patients regarding safety. 19,20 Compared to our study, RALP did show a lower transfusion rate and minimized the immediate complications, while our data did not show an extremely shortened hospital stay due to various reasons, such as institute policy and the patients' request. Implementing enhanced recovery after surgery (ERAS) protocols might be one solution that could contribute toward this outcome.…”
Section: Original Article Smjcontrasting
confidence: 77%
“…Recent research in the field suggests that a single night's stay or same-day discharge might be possible for selected patients regarding safety. 19,20 Compared to our study, RALP did show a lower transfusion rate and minimized the immediate complications, while our data did not show an extremely shortened hospital stay due to various reasons, such as institute policy and the patients' request. Implementing enhanced recovery after surgery (ERAS) protocols might be one solution that could contribute toward this outcome.…”
Section: Original Article Smjcontrasting
confidence: 77%
“…Finally, during a global pandemic (COVID-19), healthcare systems are highly strained, and access to care can be lowered; hence, overnight stays or same-day discharge for RARP (and other MIRP) are considered to be safe. 40,50,54 Other systematic reviews have addressed the effectiveness of interventions at reducing UPV in other disease sites and procedures. [88][89][90] A descriptive systematic review of 43 studies, reporting 30-day UPV reduction, by Hansen et al, ultimately found that no single intervention applied in isolation was correlated with a significant drop in 30-day UPV risk (similar to our findings).…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…Two studies with the same primary author will be included as the studies differ in geographic locations, 9,10 and only the comparative study will be included in the meta-analyses. 10 Two studies utilizing the American College of SurgeonsÒ National Surgical Quality Improvement ProgramÒ database will be included, 11,12 though only the data by Khalil et al from 2020 will be used for meta-analysis due to a larger sample size.…”
Section: Study Eligibilitymentioning
confidence: 99%
“…2e6,9e12,18e22 Study Characteristics and Quality There were 14 articles included for analysis, including 8 prospective cohort studies, 2,5,6,9,10,18,19,22 and 6 retrospective cohort studies. 3,4,11,12,20,21…”
Section: Study Identificationmentioning
confidence: 99%